The Presence of a Visual Dividing Line Increases Consumer Memory Through Attention Grabbing - Ouyang, Jun; Jia, Yanli (Frontiers in Psychology, 2022)
Marketers often use a visual line to divide the product information on an advertisement into left-right (or top-bottom) segments for aesthetic or categorization purposes. The present research examined the effect of the dividing line on the consumer memory. Across three studies (including an eye-tracking study and a field one), we showed that the presence of a dividing line enhances consumers’ memory about the products displayed on the left/top of an advertisement. This effect occurs because the dividing line orients participants’ first eye fixation to the left/top area of the advertisement, such that their visual attention is largely restricted to that area and they could better remember the contents displayed on that area. The theoretical contributions and implications for marketers and consumers are discussed.